Underground dinosaur tracksite inside a karst of southern France: Early Jurassic tridactyl traces from the Dolomitic Formation of the Malaval Cave (Lozère) - Jean-David Moreau (International Journal of Speleology, 2018)
Although underground dinosaur tracksites inside anthropic cavities such as mines or tunnels are well-known throughout the world, footprints inside natural karstic caves remain extremely rare. The Malaval Cave (Lozère, southern France) is well-known by speleologists for the abundance and the exceptional quality of acicular and helictite aragonite speleothems. Recent palaeontological prospecting inside this cave allowed the discovery of tridactyl dinosaur tracks. Here, a detailed study of theropod footprints was for the first time conducted inside a natural karstic cave, using photogrammetric imaging technique. Tracks from the Malaval Cave are located inside the “Super-Blanches” galleries. More than 26 footprints were identified. They are Hettangian in age (Lower Jurassic) and preserved as both in situ convex hyporeliefs and ex situ concave epireliefs. Tree morphotypes are distinguished, (i) “Dilophosauripus-Kayentapus” morphotype, (ii) “Eubrontes” morphotype, and (iii) “Grallatorid” morphotype. Sedimentological and mineralogical analyses of the tracksite indicate that the depositional environment varied from periodically emergent subtidal to intertidal/supratidal flat marsh. This work highlights the great interest and importance of palaeoichnological prospecting in karst caves. This is particularly true for the Causses Basin where hundreds of natural cavities were reported by speleologists in the formations yielding dinosaur traces.